A Novel Somatic Mutation of CACNA1H p.V1937M in Unilateral Primary Hyperaldosteronism - Tseng, Chi-Shin; Peng, Kang-Yung; Wang, Shuo-Meng; Tsai, Yao-Chou; Huang, Kuo-How; Lin, Wei-Chou; Hu, Ya-Hui; Wu, Vin-Cent; Chueh, Jeff S. (Frontiers in Endocrinology, 2022)
Background: Somatic mutations for excess aldosterone production have been frequently identified as important roles in the pathogenesis of unilateral primary hyperaldosteronism (uPA). Although CACNA1H mutation represents a minor etiology in primary aldosteronism, it plays a significant role in causing uPAs in sporadic cases. Objective: To identify novel somatic CACNA1H mutation in patients with uPA and investigate the pathophysiological, immunohistological, and clinical characteristics of the variant. Methods: We applied a customized and targeted gene panel next-generation sequencing approach to detect mutations from the uPA cohort in Taiwan Primary Aldosteronism Investigation study group. Information from pre-diagnostic to postoperative data was collected, including past history, medications, blood pressure readings, biochemical data, and image studies. The functional role of the variant was confirmed by in vitro studies, demonstrating aldosterone production in variant-transfected human adrenal cell lines. Results: We identiﬁed a novel somatic CACNA1H mutation c.5809G>A (p. Val1937Met) in a uPA case. The CACNA1H gene encodes the pore-forming alpha-1H subunit of the voltage-dependent T-type calcium channel Cav3.2. This somatic CACNA1H p.V1937M variant showed excellent clinical and biochemical outcomes after ipsilateral adrenalectomy. The functional effect of somatic CACNA1H p.V1937M variant results in increased CYP11B2 expression and aldosterone biosynthesis in HAC15 cells. A distinct heterogeneous foamy pattern of CYP11B2 and CYP17A1 expression was identified in immunohistological staining, supporting the pathological evidence of aldosterone synthesis. Conclusions: The somatic mutation of CACNA1H p.V1937M might be a pathogenic driver in aldosterone overproduction. This study provides new insight into the molecular mechanism and disease outcomes of uPA.